Advances in structure-hypoglycemic activity relationship and mechanisms of berry polysaccharides - Jiang-Peng, Su; Jia-Qin, Fang; Chuang, Liu; Shou-Ping, Liu; Chun, Chen; Chin-Ping, Tan; Ping-Ping, Wang; Yun-Ping, Peng; Xiong, Fu (Elsevier, 2024)
The incidence of diabetes, a serious metabolic disorder, has surged in recent decades. While conventional treatments for diabetes can have side effects and tolerability issues, natural berry polysaccharides have shown promising hypoglycemic properties with minimal side effects, offering significant potential for diabetes prevention and management. However, the connections between the sources, structures, and hypoglycemic activities of these polysaccharides have not been thoroughly discussed. This review systematically examines recent studies on the extraction, structural analysis, and hypoglycemic effects of berry polysaccharides, with a focus on their structure-activity relationships and underlying mechanisms. Generally, these findings are intended to serve as a valuable reference for future research and the application of berry polysaccharides in the functional food industry